Impact of Congenital Heart Disease on the Outcomes of Very Low Birth Weight Infants - Chen, Xuxin; Bhombal, Shazia; Kwiatkowski, David M.; Ma, Michael; Chock, Valerie Y. (American Journal of Perinatology, 2024)
Objective This study aimed to investigate the association of congenital heart disease (CHD) with morbidity and mortality of very low birth weight (VLBW) infants.Study Design This matched case–control study included VLBW infants born at a single institution between 2001 and 2015. The primary outcome was mortality. Secondary outcomes included necrotizing enterocolitis, bronchopulmonary dysplasia (BPD), sepsis, retinopathy of prematurity, and intraventricular hemorrhage. These outcomes were assessed by comparing VLBW-CHDs with control VLBW infants matched by gestational age within a week, birth weight within 500 g, sex, and birth date within a year using conditional logistic regression. Multivariable logistic regression analyzed differences in outcomes in the VLBW-CHD group between two birth periods (2001–2008 and 2009–2015) to account for changes in practice.Results In a cohort of 44 CHD infants matched with 88 controls, the mortality rate was 27% in infants with CHD and 1% in controls (p < 0.0001). The VLBW-CHDs had increased BPD; (odds ratio [OR]: 7.70, 95% confidence interval [CI]: 1.96–30.29) and sepsis (OR: 10.59, 95% CI: 2.99–37.57) compared with the control VLBWs. When adjusted for preoperative ventilator use, the VLBW-CHDs still had significantly higher odds of BPD (OR: 6.97, 95% CI: 1.73–28.04). VLBW-CHDs also had significantly higher odds of both presumed and culture-positive sepsis as well as late-onset sepsis than their matched controls. There were no significant differences in outcomes between the two birth periods.Conclusion VLBW-CHDs showed higher odds of BPD, sepsis, and mortality than VLBW infants without CHD. Future research should focus on the increased mortality and specific complications encountered by VLBW infants with CHD and implement targeted strategies to address these risks.Key Points
Keywords: congenital heart disease; preterm; very low birth weight; neonates